Effect of adding -glucan in feed on the growth rate of White Snapper (Lates calcarifer) fingerling - Adli Waliul Perdana; Siska Mellisa; Jadi Yakin Hotmartupa Siahaan; Iko Imelda Arisa; Sayyid Afdhal El Rahimi; Firman M. Nur; Siti Maulida (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
White snapper Lates calcarifer is one of the marine fish commodities that has important economic value. The addition of immunostimulant ingredients in feed is believed to increase immunity and increase fish growth. This study aims to determine the effect of adding -glucan to feed on white snapper (Lates calcarifer). This study used a completely randomized design (CRD) consisting of 5 treatments with 3 repetitions. White snapper used with a weight of 6 grams and a length of 7. The frequency of feeding is done 3 times a day. The results of the ANOVA test showed that the addition of -glucan in the feed significantly affected the growth rate of the fry of white snapper (Lates calcarifer) (P0.05). The best treatment in this study was treatment E (commercial feed + -glucan 8g/kg feed) which gave the best growth in White snapper where this treatment was able to increase absolute weight (4.51 0.29), absolute length (4 .84 0.284), specific growth rate (2.09 0.15), FCR (1.00 1.00), feed utilization efficiency (97.42 0.50) and survival (100.00 0.00).